Informasi Spasial Perubahan Tutupan Lahan untuk Pengelolaan Wilayah di Kecamatan Mataraman - Bahrul Ilmi; Efrinda Ari Ayuningtyas; Wisnu Putra Danarto; Indra Agung Pamuja (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2026)
Land cover change is an important indicator of environmental dynamics because it is closely associated with ecological function alteration, ecosystem degradation, and the sustainability of land resource utilization. Mataraman District, Banjar Regency, South Kalimantan, has experienced rapid expansion of oil palm plantations and mining activities that potentially affect environmental conditions and landscape structure. However, spatial information regarding the location, extent, and direction of land cover change remains limited, highlighting the need for more detailed information to support environmental monitoring and regional management. This study aimed to develop spatial information on land cover change from 2020 to 2025 using Sentinel-2 imagery and the Random Forest algorithm within the Google Earth Engine platform. The analysis was conducted through land cover classification, change detection, and transition matrix approaches to identify changes in area, spatial distribution, and conversion patterns among land cover classes. The results showed that secondary forest decreased by 6,026.04 ha (-30.22%), while oil palm plantations and mining areas increased by 4,422.16 ha (+22.18%) and 1,606.97 ha (+8.06%), respectively. The largest land cover conversion occurred from secondary forest to oil palm plantations, covering 4,069.57 ha, followed by secondary forest to mining areas, covering 1,537.75 ha. Change status analysis indicated that approximately 8,736.12 ha, or 44% of the total area of Mataraman District, experienced land cover change during the observation period. The spatial information generated provides a detailed representation of land cover dynamics and can serve as a supporting reference for environmental monitoring, land-use evaluation, and more adaptive regional management in response to land use change.